Osteogenic activity of bone: Novel approach of polyvinylidene fluoride films, marrow blood supply, and ultrasound stimulation - Zuchuat, Jésica Itatí (2023)
Electric fields used in bone stimulation are based on the application of direct current, but some drawbacks exist, such as the need for an external power source. Piezoelectric poly(vinylidene fluoride) (PVDF) has attracted interest for biomedical applications due to its flexibility, low toxicity, and the piezoelectric response to mechanical stimuli. This study aimed to investigate the effects of PVDF films on bone regeneration in rabbit tibias to assess the potential improvement in osteogenesis. An initial exploratory experiment was performed to determine optimal parameters for regulating the marrow blood supply. The second experiment focused on examining the effects of ultrasound stimulation on the implant's osteogenic capacity. The results showed that PVDF films have a notable impact on the extraskeletal bone formation and bone density in a secluded microenvironment with and without microperforations. At 60 days after surgery, tibias with marrow blood supply reached higher bone volumes and density and they were consistent with the cellular activity. Our results suggest that piezoelectric PVDF films have osteogenic characteristics and can be used to enhance new bone formation in a secluded space, thus reinforcing their biocompatibility nature. Additional studies are required to analyze the benefits of ultrasound stimulation.